Penerapan Problem Based Learning untuk Meningkatkan Keterampilan Menulis Teks Cerita Pendek - Nurfaizin, Irham; Astuti, Cutiana Windri; Suprapto, Suprapto (STKIP PGRI Ponorogo Press, 2024)
The purpose of this study is to describe the application of the Problem Based Learning model to improve the writing skills of short story texts to class XI Ma Plus Wali Songo Madiun students in the 2022/2023 Academic Year. The background of this Classroom Action Research (CAR) is the low level of student writing skills, especially short story text. The low skills to write short story texts are caused by student learning interest in writing low, as well as lack of learning motivation. To improve student short story text skills, efforts made using the Problem Based Learning learning model. With PBL students can feel the benefits of learning because the problems that are resolved are directly associated with real life. This can increase student motivation and interest in the material being studied. This classroom action research was conducted at Ma Wali Songo Madiun, with class XI Mia subjects, consisting of 40 students, 17 male students and 23 female students. This classroom action research was carried out in three cycles. Each cycle there are four stages consisting of planning, implementation, observation and reflection. Meanwhile, for data collection techniques in this study in the form of tests and observation sheets. The results show that the use of the Problem Based Learning model can improve the writing skills of the short story text of class XI saince MA Plus Wali Songo. The percentage of completeness in cycle I is 50%cycle II 72.5%, and cycle III 97.5%.